First Report of Protein and Fat Level of Alabio Duck (Anas platyrhynchos Borneo) Eggs in Hulu Sungai Utara, Indonesia for Improving Human Health - Rini Fajarwati1 , Arif Nur Muhammad Ansori2 , Sri Pantja Madyawati3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Indonesian local ducks are native germplasm of Indonesia which has the genetic quality and has the potentialto be developed as a productive egg producer. Each type of duck has a different chemical compositionin their eggs. The purpose of this study is to find out the levels of protein and fat in Alabio duck (Anasplatyrhynchos Borneo) eggs in Hambuku Raya Village and Putat Atas Village, Hulu Sungai Utara, SouthKalimantan, Indonesia. This study used a completely randomized design (CRD). Interestingly, we showedthat the level of protein and fat in Alabio duck eggs was relatively good. Therefore, this finding is the basicdata for further research on Alabio duck in the future.